An application of optimized Otsu multi-threshold segmentation based on fireworks algorithm in cement SEM image. (August 2018) - Liu, Wei; Shi, Heng; He, Xingyang; Pan, Shang; Ye, Zhiwei; Wang, Yingbin
In order to facilitate the study of the structure of cement components, this paper uses image processing technology to achieve multi-threshold segmentation for cement scanning electron microscope image under different conditions and applies an optimized Otsu multi-threshold segmentation based on fireworks algorithm. The method designs fitness function with Otsu multi-threshold segmentation method and searches optimal solution by iteration with the fireworks algorithm. Finally, the search problem of optimization is transformed into a multi-variable solution. The experimental results show that this method can achieve the same result as the classical algorithm and it has better convergence and stability, and the method can be widely used in many fields.